Проблемы современной электротехники на пути создания новых источников энергии - Кузьмин, Виктор Владимирович (НТУ "ХПИ", 2005)
В статье рассмотрены проблемы современной теории электричества (противоречия и парадоксы), затрудняющие разработку научных основ для создания источников энергии нового поколения.

The paper considers problems of current theory of electricity (contradictions and paradoxes) that complicate development of scientific foundations for new-generation energy sources creation.
Problems of state-of-the-art electric engineering on the way toward new energy sources creation
Keywords: теория электричества; электротехника; нетрадиуионная электроэнергетика; энергетика; electricity theory; energy; paradoxes; new-generation; sourses; contradictions